MODEL STAR DENGAN BOBOT SERAGAM SEBAGAI PENDETEKSI DEBIT AIR SUNGAI CITARUM - Kankan Kankan Parmikanti; Khafsah Joebaedi; Iin Irianingsih (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2016)
Lately when rainfall in West Java is quite high, the problem of flooding caused by overflowing of the river has always been a trending topic of regional leaders. Whatever the causes of flooding, be it because a lot of waste dumped in rivers or due to illegal logging of trees in the forest, the river water discharge increased rapidly, and overflowed into public housing. Based on the above, it should be made a model that can predict the water discharge of the river from time to time in various locations in West Java. In this paper will be presented studies Space Time Auto Regression models STAR (1,1) to model the problem of water discharge some rivers in West Java, which can be useful for predicting the discharge of river water in the future. By using Least Squares Method as predictors for the parameters, as well as assuming a uniform weighting matrix, the result that the water discharge of a river in addition affected by the river water flow at an earlier time, it is also influenced by the discharge of river water around.